PENGARUH BRAND IMAGE, CUSTOMER LOYALTY, DAN HOST LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN PLATFORM SHOPEE LIVE - Saputry, Riny Andriani; Napitupulu, Elfrida Viesta (STMIK Pringsewu, 2025)
Online shopping is increasingly important to modern consumers, with Live Streaming as a marketing innovation on e-commerce platforms such as Shopee. This feature allows sellers to demonstrate products live, increase interaction, and provide a unique shopping experience. This study uses a questionnaire to Shopee Live users and analyzes the data with the t test and f test through SPSS to evaluate the effect of Brand Image, Customer Loyalty, and Live Streaming Host on purchasing decisions. The results show that all three factors significantly influence purchasing decisions, with a positive Brand Image increasing consumer trust and Customer Loyalty encouraging emotional commitment. In addition, professional and interactive hosts also play an important role in building trust and a pleasant atmosphere for consumers. The findings provide insights for marketers in designing more effective marketing strategies in the digital age.